In-flight Management for Attitude Control System with Animation of Satellite Motion - Somov, Ye.; Butyrin, S.; Somov, S.; Somova, T.; Hajiyev, C.; Sukhanov, V. (Elsevier BV, 2016)
Abstract Contemporary land-survey satellites are placed onto the orbit altitudes from 600 up to 1000 km. For such spacecraft we consider some principal problems on the spacecraft attitude digital and pulse-width control and present elaborated methods for in-flight identification, verification and management of attitude control system with animation of satellite motion.